Usage factors for phone application among Generation-Y in UiTM Malacca City Campus / Arsyad Nordin - Nordin, Arsyad (Faculty of Business and Management, 2012)
In the field of telecommunication, smartphone has become one of the main medium or products for consumers all around the world. Thus, a study of the smartphone application is carried out to see the matters at hand. The title of this research paper is “Usage Factors For Phone Application Among Generation Y In UiTM Malacca City Campus”. The purpose of this research is to see the relationship between the variables that is the dependent variable and the independent variables. There are three independent variables that are involved in this research which are social influences, knowledge, and consistent entertainment. Meanwhile, the dependent variable is to investigate the usage of phone application among Generation Y in UiTM Malacca City Campus. In order to achieve this research, the hypothesis focuses on the objective to identify whether there are relationship between social influences, knowledge, and consistent entertainment towards the usage of phone application among Generation Y in UiTM Malacca City Campus. In gathering the data, a set of questionnaire was distributed to Generation Y in UiTM Malacca City Campus. Questionnaires were distributed to 100 respondents of the Generation Y. The objective of this research is to determine the to determine the relationship between social influences and usage of phone application, to determine the relationship between knowledge and usage of phone application, to determine the relationship between consistent entertainment and usage of phone application and To identify which independent variables that has the strongest effect towards usage of phone application.